Genome‐scale signatures of adaptive gene expression changes in an invasive seaweed Gracilaria vermiculophylla. Issue 3 (20th November 2022) - Xiang, Jin‐Xi; Saha, Mahasweta; Zhong, Kai‐Le; Zhang, Quan‐Sheng; Zhang, Di; Jueterbock, Alexander; Krueger‐Hadfield, Stacy A.; Wang, Gao‐Ge; Weinberger, Florian; Hu, Zi‐Min
Abstract: Invasive species can successfully and rapidly colonize new niches and expand ranges via founder effects and enhanced tolerance towards environmental stresses. However, the underpinning molecular mechanisms (i.e., gene expression changes) facilitating rapid adaptation to harsh environments are still poorly understood. The red seaweed Gracilaria vermiculophylla, which is native to the northwest Pacific but invaded North American and European coastal habitats over the last 100 years, provides an excellent model to examine whether enhanced tolerance at the level of gene expression contributed to its invasion success. We collected G. vermiculophylla from its native range in Japan and from two non‐native regions along the Delmarva Peninsula (Eastern United States) and in Germany. Thalli were reared in a common garden for 4 months at which time we performed comparative transcriptome (mRNA) and microRNA (miRNA) sequencing. MRNA‐expression profiling identified 59 genes that were differently expressed between native and non‐native thalli. Of these genes, most were involved in metabolic pathways, including photosynthesis, abiotic stress, and biosynthesis of products and hormones in all four non‐native sites. MiRNA‐based target‐gene correlation analysis in native/non‐native pairs revealed that some target genes are positively or negatively regulated via epigenetic mechanisms. Importantly, these genes are mostly associated with metabolism and defence capability (e.g., metal transporter Nramp5, senescence‐associated protein, cell wall‐associated hydrolase, ycf68 protein and cytochrome P450‐like TBP). Thus, our gene expression results indicate that resource reallocation to metabolic processes is most likely a predominant mechanism contributing to the range‐wide persistence and adaptation of G. vermiculophylla in the invaded range. This study, therefore, provides molecular insight into the speed and nature of invasion‐mediated rapid adaption.